The Impact of Countries’ Artificial Intelligence Readiness Levels on New Business Establishment: Controlling for Energy Consumption, Economic Growth, Inflation, and Population - Zharkimbekova, Kamila S.; Niyazbekova, Roza K.; Yessirkepova, Altyn M.; Baineyeva, Parida; Kanashayev, Daulet; Khassenova, Laura A.; Bolganbayev, Artur (International Journal of Energy Economics and Policy, 2026)
This study empirically examines how a country’s AI readiness level affects the establishment of new businesses while controlling for key macroeconomic variables such as energy consumption, economic growth, inflation, and population growth. It specifically highlights Kazakhstan, a country with significant potential for digital transformation and entrepreneurial development, to clarify the relationship between AI readiness indicators and new business startups at the national level. The analysis utilizes subcomponents of the AI Preparedness Index (AIPI) developed by the International Monetary Fund, which includes digital infrastructure, innovation and economic integration, human capital and labor market policies, and regulation and ethics indicators. The World Bank’s “Starting a Business” index is used as a measure of new business establishments. By employing secondary data from various countries, hierarchical regression is applied to assess the additional explanatory power of AI-related indicators on new business formation in a stepwise fashion. The findings indicate that macroeconomic variables such as economic growth, energy consumption, inflation, and population growth have a statistically limited impact on the new business establishment index. In contrast, all sub-indices related to artificial intelligence readiness exert positive and significant effects on new business establishment. Notably, the dimensions of digital infrastructure and regulatory and ethical considerations demonstrate higher explanatory power and effect size. The results underscore that entrepreneurial activity is influenced not only by macroeconomic conditions but also by digital, technological, and institutional capabilities. Therefore, this study emphasizes that AI readiness has become a crucial structural component supporting new business establishment and offers important implications for digital transformation and entrepreneurship policies.